Designing a Diversified Indian Mustard Production System for Energy‐Carbon‐Cum‐Heat Use Efficiency and Sowing Dates Assessment - Sunil Kumar; Ram Swaroop Meena; Sandeep Kumar; Gourisankar Pradhan; Chetan Kumar Jangir; Shambhunath Ghosh; Himani Punia; Parvender Sheoran; Ramawatar Meena; Md. Afjal Ahmad; Suneel Kumar Goyal; Nazih Y. Rebouh (GCB Bioenergy)
ABSTRACT The rice (Oryza sativa L.)–wheat (Triticum aestivum L.) cropping system faces major challenges such as stagnant yields, high input and energy demands, and increasing soil and air pollution. Indian mustard (Brassica juncea L.) is a promising crop for diversification within rice‐based ecosystems. The objective of this study was to evaluate the effects of different sowing dates and nutrient sources on energy budgeting in diversified Indian mustard and to assess the impact of these nutrient sources on heat‐cum‐carbon efficiency. The experiment was conducted using a split‐plot design (SPD) with three sowing dates—November 17, November 27, and December 07—in the main plots, and eight nutrient sources in the subplots, where the recommended dose of fertilizer was 100 N:50 P2O5:50 K2O:40 S kg ha−1. The results, based on pooled data, indicated that among the sowing dates, November 17 recorded the highest values for several key metrics. These include energy use efficiency (EUE: 3.46, 5.12, and 12.16), energy production (EP: 0.152, 0.41, and 0.56 kg MJ−1), net energy (NE: 29,712, 50,483, and 92,558 MJ ha−1), energy profitability (EPr: 2.46, 2.88, and 6.34), human energy profitability (HEP: 364.82, 412.60, and 777.42), energy output efficiency (EOE: 364.69, 412.49, and 777.18 MJ d−1), carbon output (CO: 815, 2215, and 3030 kg CE ha−1), carbon efficiency (CE: 2.07, 5.59, and 7.66), and carbon sustainability index (CSI: 1.07, 4.59, and 6.66) for seed, stover, and biological yield, respectively, compared to the crops sown on November 27 and December 07. The study also revealed significant increases in heat use efficiency (HUE) on dry matter at 45 and 90 days after sowing (DAS) and on seed, stover, and biological yield (13.3, 8.46, 1.52, 4.16, and 5.69 kg ha−1°C days, respectively). In the subplots, the highest EUE (3.92, 5.10, and 12.1), EP (0.172, 0.408, and 0.58 kg ha−1), and EPr (2.92, 2.86, and 6.78) for seed, stover, and biological yield were observed in the control treatment, outperforming the other nutrient sources on a pooled basis. The highest SE production (8.59, 3.48, and 2.47 MJ kg−1) for seed, stover, and biological yield was recorded with the application of 100% of the recommended dose of fertilizer (RDF) combined with Azotobacter and phosphorus‐solubilizing bacteria (PSB). Furthermore, the highest NE (35,427, 52,203, and 102,370 MJ ha−1), HEP (434.02, 438.67, and 872.68), EOE (448.37, 452.68, and 901.04 MJ d−1), CO (972, 2359, and 3331 kg CE ha−1), CE (2.48, 6.01, and 8.48), CSI (1.48, 5.01, and 7.48), and HUE (1.67, 4.12, and 5.81 kg ha−1°C days) for seed, stover, and biological yield were observed with the application of 75% RDF + 25% nitrogen from pressmud, combined with Azotobacter and PSB. This study provides a novel framework for optimizing sowing dates and nutrient sources that can lead to the development of an energy‐efficient, heat‐cum‐carbon‐efficient, and eco‐friendly production system. Its findings offer scalable solutions for enhancing sustainability and reducing environmental footprints in rice‐based cropping systems.